The summer guests - Gerritsen, Tess; Child, Lee (Seattle : Thomas & Mercer, 2025)
In Purity, Maine, former spy Maggie Bird and her Martini Club of ex-CIA operatives are drawn into the search for a missing teen with ties to their past, as they confront an innocent friend's wrongful suspicion, a buried corpse, and dark secrets that threaten to unravel everything they've worked to protect.
Includes short story Over easy by Lee Child and Tess Gerritsen.
Maine author.
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Fiction; Women spies -- Fiction; Retirees -- Fiction; Missing person -- Fiction; Book clubs (Discussion groups) -- Fiction; Maine -- Fiction; Thrillers (Fiction); Spy fiction